The haunted serpent - Mitchell, Dora M. (Sterling Children's Books, 2018)
New kid in school Spaulding Meriwether teams with cool kid Marietta, her euphonium-playing sister Lucy, and popular jock Kenny to investigate a mysterious boa constrictor that lives next door to Spaulding that may have eaten its owner.